Analisis Kepuasan Konsumen Terhadap Kualitas Produk Dan Pelayanan ACK Fried Chicken Di Banjar Dinas Latu Sari Abiansemal - Tuningrat, Ida Ayu Mahatma; Wedhana, Ida Bagus Gede Dika; Wiranatha , Anak Agung Putu Agung Suryawan; Hartiati, Amna (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
The abundance of fast-food restaurants has led to competition in the quality of products and services offered, including at the ACK Fried Chicken Latu Sari fast-food restaurant. The purpose of this research is to analyze the level of consumer satisfaction with the product and service quality of ACK Fried Chicken Latu Sari and to determine the attributes of product and service quality that need to be improved or maintained by ACK Fried Chicken Latu Sari. This research was conducted through literature study, interviews with the owner of ACK Fried Chicken Latu Sari, and distributing questionnaires to 90 respondents. Then, the data results in this study were analyzed using the Importance Performance Analysis (IPA) method. The research results show that the attribute with the highest level of suitability for product quality is the attractive presentation/plating at 103.5%, and the lowest attribute is the price of the food in relation to its quality at 97.02%. Meanwhile, the attribute with the highest level of suitability for service quality is the availability of facilities (toilet, smoking area, wifi) at 101.8%, and the lowest attribute is customer comfort while at ACK Fried Chicken at 97.00%.